Critical Analysis of the Shift in PAI Curriculum From the 2013 Curriculum to the Merdeka Curriculum: Opportunities and Challenges of Implementation - Siti Chodijah; Umi Sifatul Rofiah; Nurul Mubin (Al Yazidiy Jurnal Sosial Humaniora dan Pendidikan, 2026)
This study aims to conduct a critical analysis of the paradigm shift in Islamic Education (PAI) from the 2013 Curriculum (K-13) to the Kurikulum Merdeka (Independent Curriculum). The primary focus of this research is to identify optimizable opportunities and strategic challenges faced by educators and educational institutions during the implementation process. The methodology employed is a qualitative approach using the library research method, where data were collected through documentation studies and processed using content analysis techniques. The results indicate fundamental differences between the two curricula, starting with a structural transformation from the rigid, competency-based structure of Core Competencies (KI) and Basic Competencies (KD) in K-13 to a more flexible framework based on Learning Outcomes (CP) per phase in Kurikulum Merdeka. This shift provides opportunities for pedagogical innovation, such as differentiated learning and character development through the Project for Strengthening the Profile of Pancasila Students (P5), which enhances the relevance of PAI materials through a more adaptable approach. However, field implementation faces challenges including educators' psychological readiness (culture shock), complexities in designing authentic formative assessments, and a digital literacy gap in utilizing the Platform Merdeka Mengajar (PMM). The critical analysis concludes that while Kurikulum Merdeka offers a more humanistic and contextual educational transformation, its success heavily depends on systemic support, continuous training, and intensive mentoring for teachers. Practically, this study implies that PAI educators must prioritize peer-mentoring through teacher communities and maximize the use of PMM to bridge the digital literacy gap, ensuring that this change does not become a mere administrative formality.